Systemic Lupus Erythematosus Pathogenesis and Management - Lionaki, Sophia (IntechOpen, 2023)
This Edited Volume "Systemic Lupus Erythematosus - Pathogenesis" and Management" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of lupus erythematosus. The book comprises single chapters authored by various researchers and edited by an expert active in the lupus research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on lupus, and open new possible research paths for further novel developments.